Nonlinear thermo-mechanical coupled analysis of high temperature effect on strength, contact stress and ultimate torque of tool joint. (December 2020) - Cheng, Jinhua; Sun, Youhong; Yu, Yongping; Chen, Lihui; Ma, Xiaolong
Abstract: In this study, a NC35 tool joint with double shoulder is considered as the research object and studied by finite element method (FEM) using nonlinear thermo-mechanical coupled model and implicit & explicit conversion method. Von mises stress field, temperature field, contact stress, and ultimate working torque of tool joint under different axial loads at high temperatures are calculated and compared with those at normal atmospheric temperature. High temperature doesn't change the stress and contact stress distribution under make-up torque condition but reduces the value of stress and contact stress due to material properties decline. Ultimate working torque decreases with the increase of temperature under the same axial load. Coupled influence of axial load and temperature on shoulder contact state is analyzed. Furthermore, failure modes of tool joint under different temperatures and axial loads are discussed. According to the results of calculation, a guiding diagram considering safety factor is presented which can provide a safe operating range at normal atmospheric temperature and high temperature. It can help engineers choose appropriate operating parameters under different conditions. Highlights: Effect of high temperature on mechanical properties of double-shoulder tool joint. A 3D thermal-mechanical coupled elastoplastic FE model for tool joint is presented. The effects of heat on contact stress, stress and failure mode are analyzed. The coupling effects of torque, tension and heat on limit operating load are studied. Limited operating load profiles for different temperatures are proposed.